Rozwiązane

Wykonaj Odejmowanie
a) (3xy-5x²y)-(10xy -2x²y) =
b) (-12abc-4a²bc)-(abc+a²bc)+12 =
c) (1⅗x³+⅔ y²-⅚)-(2,4x³+y²-1⅙)=
d) (0,5x²y²-⅔ab-1)-(-⅓x²y²+jedna dwunasta ab-¼) =



Odpowiedź :

Eddiss
a) (3xy-5x²y)-(10xy -2x²y) = 3xy-5x²y-10xy +2x²y=-7xy-3x²y
b) (-12abc-4a²bc)-(abc+a²bc)+12 =
= -12abc-4a²bc-abc-a²bc+12= -13abc-5a²bc+12
c) (1⅗x³+⅔ y²-⅚)-(2,4x³+y²-1⅙)=1⅗x³+⅔ y²-⅚-2,4x³-y²+1⅙=
=(8/5)x³ + ⅔ y² -⅚ -(12/5) x³-y²+ 7/6=
=(-4/5)x³- (1/3)y²+1/3
d) (0,5x²y²-⅔ab-1)-(-⅓x²y²+1/12 ab-¼) =0,5x²y²-⅔ab-1+⅓x²y²-1/12 ab+¼=
=3/6x²y²-(8/12)ab-1+(2/6)x²y²-1/12 ab+¼=(5/6)x²y²-(9/12)ab-3/4=(5/6)x²y²-(3/4)ab-3/4